Learning to Read Increases the Informativeness of Distributed Ventral Temporal Responses. (28th August 2018) - Nordt, Marisa; Gomez, Jesse; Natu, Vaidehi; Jeska, Brianna; Barnett, Michael; Grill-Spector, Kalanit
Abstract: Becoming a proficient reader requires substantial learning over many years. However, it is unknown how learning to read affects development of distributed visual representations across human ventral temporal cortex (VTC). Using fMRI and a data-driven, computational approach, we quantified the development of distributed VTC responses to characters (pseudowords and numbers) versus other domains in children, preteens, and adults. Results reveal anatomical- and hemisphere-specific development. With development, distributed responses to words and characters became more distinctive and informative in lateral but not medial VTC, and in the left but not right hemisphere. While the development of voxels with both positive and negative preference to words affected distributed information, only development of voxels with positive preference to words (i.e., word-selective) was correlated with reading ability. These data show that developmental increases in informativeness of distributed left lateral VTC responses are related to proficient reading and have important implications for both developmental theories and for elucidating neural mechanisms of reading disabilities.